Endogenous cortisol levels are associated with an imbalanced striatal sensitivity to monetary versus non-monetary cues in pathological gamblers - Li, Yansong; Sescousse, Guillaume; Dreher, Jean-Claude (Frontiers in Behavioral Neuroscience, 2014)
Pathological gambling is a behavioral addiction characterized by a chronic failure to resist the urge to gamble. It shares many similarities with drug addiction. Glucocorticoid hormones including cortisol are thought to play a key role in the vulnerability to addictive behaviors, by acting on the mesolimbic reward pathway. Based on our previous report of an imbalanced sensitivity to monetary versus non-monetary incentives in the ventral striatum of pathological gamblers (PGs), we investigated whether this imbalance was mediated by individual differences in endogenous cortisol levels. We used functional magnetic resonance imaging (fMRI) and examined the relationship between cortisol levels and the neural responses to monetary versus non-monetary cues, while PGs and healthy controls were engaged in an incentive delay task manipulating both monetary and erotic rewards. We found a positive correlation between cortisol levels and ventral striatal responses to monetary versus erotic cues in PGs, but not in healthy controls. This indicates that the ventral striatum is a key region where cortisol modulates incentive motivation for gambling versus non-gambling related stimuli in PGs. Our results extend the proposed role of glucocorticoid hormones in drug addiction to behavioral addiction, and help understand the impact of cortisol on reward incentive processing in PGs.